2019
DOI: 10.1002/dvg.23347
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila pericentrin‐like protein promotes the formation of primordial germ cells

Abstract: Summary Primordial germ cells (PGCs) are the precursors to the adult germline stem cells that are set aside early during embryogenesis and specified through the inheritance of the germ plasm, which contains the mRNAs and proteins that function as the germline fate determinants. In Drosophila melanogaster, formation of the PGCs requires the microtubule and actin cytoskeletal networks to actively segregate the germ plasm from the soma and physically construct the pole buds (PBs) that protrude from the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In control embryos, Cnn radiates symmetrically from centrosomes, forming interphase-specific flares, as previously described (Figure 4C, WT) (Megraw et al, 2002). Consistent with our prior work, Cnn distribution appears severely disorganized in plp embryos with fragmented Cnn flares and Cnn puncta dispersed within the cytosol (Figure 4C, plp) (Lerit et al, 2015;Fang and Lerit, 2020). Quantification of the relative number of cytoplasmic Cnn puncta in segmented images shows a significant, nearly 6-fold increase in Cnn puncta in plp embryos, as compared to WT (Figure 4D).…”
Section: Orb Regulates Plp-cnn Scaffold Organizationsupporting
confidence: 90%
See 1 more Smart Citation
“…In control embryos, Cnn radiates symmetrically from centrosomes, forming interphase-specific flares, as previously described (Figure 4C, WT) (Megraw et al, 2002). Consistent with our prior work, Cnn distribution appears severely disorganized in plp embryos with fragmented Cnn flares and Cnn puncta dispersed within the cytosol (Figure 4C, plp) (Lerit et al, 2015;Fang and Lerit, 2020). Quantification of the relative number of cytoplasmic Cnn puncta in segmented images shows a significant, nearly 6-fold increase in Cnn puncta in plp embryos, as compared to WT (Figure 4D).…”
Section: Orb Regulates Plp-cnn Scaffold Organizationsupporting
confidence: 90%
“…In orb mutant embryos, we observed PLP protein is ~50% downregulated (Figure 3A, E). We recently showed plp hemizygote embryos (plp 2172 /+) also result in an average ~50% downregulation of PLP protein (Fang and Lerit, 2020). Therefore, we generated plp 2172 , orb F343 recombinant chromosomes and crossed these animals to orb mel mutants to harvest embryos from plp hemizygous, orb mutant mothers (genotype: plp 2172 /+, orb F343 /orb mel ; hereafter, plp/+, orb).…”
Section: Orb Promotes Plp Translationmentioning
confidence: 99%
“…The presence of gNAC in the cytoplasm of pole cells has been expected, it was also preserved in the centrosomes of pole cells, the precursors of germ cells. It has been reported that the centrosome proteins participate in the organization and development of the primordial germ cells (Fang and Lerit, 2020) and centrosome nucleated microtubules facilitate germ plasm partitioning between proliferating primordial germ cells, which are highly sensitive to the dosage of germ plasm components (Lerit and Gavis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both gNAC and the germinal marker, the VASA protein, can be detected in the cytoplasm of primordial germ cells and their precursors migrating to the sites of gonad formation. The importance of the presence of gNAC in embryonic syncytial centrosomes is highlighted by recent results revealing the critical role of centrosomes in the development of pole buds and pole cells and the formation of microtubules involved in the proper distribution of germplasm components in primordial germ cells (Lerit and Gavis, 2011; Fang and Lerit, 2020) and in protein interactions (Nishi et al, 2014; Koike et al, 2020; Rieloff and Skepo, 2020). We speculate that these events may be closely supported by a specific germline proteostasis network involving gNACs as internally disordered proteins carrying phosphosites.…”
Section: Introductionmentioning
confidence: 99%
“…Human PCNT and Drosophila Pcnt-like protein (Plp) share functionally conserved roles in PCM scaffolding and microtubule nucleation [23][24][25][26][27][28]. In humans, loss-of-function PCNT mutations are associated with microcephalic osteodysplastic primordial dwarfism type II (MOPD II), as well as cardiac and neurovascular abnormalities [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%